The United States - Jennings, Jerry E.; Smith, Marion Hagens; Havighurst, Walter (Fideler social studies, 1979)
The people, geography and history of the United States. The Northeast, The South, Midwest and Great Plains, The West, Pictorial Story of Our Country. Depth Studies.